Bergenin as a Novel Urate-Lowering Therapeutic Strategy for Hyperuricemia - Chen, Mo; Ye, Chenyi; Zhu, Jianing; Zhang, Peiyu; Jiang, Yujie; Lu, Xiaoyong; Wu, Huaxiang (Frontiers in Cell and Developmental Biology, 2020)
Bergenin is a C-glucoside of 4-O-methyl gallic acid isolated from several medicinal plants and has multiple biological activities. The aim of this study was to assess the potential usefulness of bergenin in hyperuricemia. We found that bergenin reduced serum urate levels in hyperuricemic mice by promoting renal and gut uric acid excretion. Bergenin treatment increased ABCG2 expression both in the kidneys and intestine, while the expression of SLC2A9 was suppressed in the kidney and increased in the intestine. Moreover, bergenin induced ABCG2 expression in HK-2 and Caco-2 cells, as well as SLC2A9 in Caco-2 cells, via the activation of PPARγ. Nevertheless, bergenin suppressed SLC2A9 expression in HK-2 cells by inhibiting the nuclear translocation of p53. Furthermore, bergenin decreased the serum levels of IL-6, IL-1β, and TNF-α in hyperuricemic mice, and promoted a polarization shift from the M1 to M2 phenotype in RAW264.7 cells. In conclusion, these findings provide evidence supporting the further development of bergenin as a novel therapeutic strategy for hyperuricemia.